IT and Profitability of Indian Banking Industry in Transitional Period - Uppal, R.K.; Kaur, Rimpi (Gyan Management Journal, 2008)
In the post-reforms period, Indian banking is passing through crucial stage. There is a paradigm shift in different parameters of transformation. Many internal and external factors are responsible for this bank transformation. A huge competition (inter and intra-bank groups), global forces are compelling the banks to make radical change in their day to day functioning. WTO, af).other dimension forcing the banks to make internal and external change to meet the e-age challenges. IT is a crucial parameter for transformation in bank structure, work - culture, functioning, HRD and business re-engineering. Ebanking services are replacing the traditional services and creating a new scale in transformation. In the initial stage, e-channels where introduced in metropolitan cities and urban areas but recently some banks especially new private sector banks have started capturing rural and semi-urban areas too.